Effects of the landline telephone filter and linguistic context on speaker-dependent variability in /s/ - Smorenburg, Laura; Heeren, Willemijn (International Journal of Speech, Language and the Law, 2023)
Previous research has demonstrated that vowel formants situated near the lower limit of the bandwidth show effects of the telephone filter (Künzel 2001; Byrne and Foulkes 2004). In this work, the effects of the landline telephone filter are examined for one consonant, namely fricative /s/. Although this speech sound is expected to show large effects of narrowband telephone filters due to its high-frequency spectral characteristics, previous work on Dutch telephone speech showed that, despite its compromised acoustics, /s/ still contains considerable amounts of speaker information (Smorenburg & Heeren, 2021). Using English data that were simultaneously recorded as broadband and telephone speech, this work shows large effects of the telephone filter on both the acoustics and linear discriminant analysis (LDA) speaker classification. Linguistic effects were only observable in studio recordings and generally did not have an effect on the speaker classification with one exception: when the following context is labial, LDA speaker-classification accuracy was higher, indicating idiosyncrasies in anticipatory labial coarticulation.